Start-Up Team (Institutional Knowledge at Singapore Management University, 1998)
The team working on the start-up of Singapore Management University. Standing, left to right: Professor Tan Chin Tiong, Associate Professor Low Aik Meng, Associate Professor Tsui Kai Chong, Deputy Director of Human Resources Wang Siew Fu, Associate Professor Leong Kwong Sin, Associate Professor Pang Yang Hoong, Associate Professor Toh Tian Ser, and Associate Professor Low Kee Yang. Seated, left to right: Professor Tan Teck Meng and Ho Kwon Ping, Executive Committee chairman and Campus Development Committee chairman. Picture was taken at Wah Chang House in late 1998.